Effects of temperature and live prey concentration on Colossoma macropomum larviculture - Fabio Aremil Costa dos Santos; Gustavo Soares da Costa Julio; André de Sena Souza; Pedro Paulo Cortezzi Pedras; Ronald Kennedy-Luz (Revista MVZ Cordoba)
Objective. The study evaluated the performance and survival of Colossoma macropomum larvae at different temperatures and concentrations of prey. Materials and methods. Two temperatures (28 and 32ºC) (T) and two initial daily concentrations (500 and 1,000 Artemia nauplii per larva) (CP) of prey were used. These concentrations were increased every 5 days during the first 15 days of cultivation. From the 16th to the 30th day, the larvae received exclusively a commercial diet. Results. In the first 7 days, weight (P), total length (TL) and daily specific growth rate (SGR) were higher for T32 treatments (p<0.05). After 15 days, P, TL and SGR were higher for CP1000 (p<0.05). After 22 days, P and TL suffered the effect of the initial concentration of prey and water temperature with higher values for CP1000 and T32 (p<0.05). At the end of 30 days of cultivation, P was affected only by water temperature with higher values for T32 (p<0.05). The TL showed an effect of temperature and initial concentration of prey with higher values for CP1000 and T32 (p<0.05). During feeding with a commercial diet (days 16-30 of cultivation), survival was higher for T32 (94.38±6.12%) (p<0.05), with no difference for initial prey concentration. Conclusions. It is concluded that the larviculture of C. macropomum must be carried out with a temperature of 32° C and that the food management must be differentiated during the first 15 days, positively influenced in the period of feeding with ration.